Prognosis and Prophylactic Regional Nodal Irradiation in Breast Cancer Patients With the First Isolated Chest Wall Recurrence After Mastectomy - Zhao, Xu-Ran; Xuan, Liang; Yin, Jun; Tang, Yu; Sun, Hui-Ru; Jing, Hao; Song, Yong-Wen; Jin, Jing; Liu, Yue-Ping; Fang, Hui; Ren, Hua; Chen, Bo; et al. (Frontiers in Oncology, 2021)
Background and purpose: Optimal radiation target volumes for breast cancer patients with their first isolated chest wall recurrence (ICWR) after mastectomy are controversial. We aimed to analyze the regional failure patterns and to investigate the role of prophylactic regional nodal irradiation (RNI) for ICWR. Materials and methods: Altogether 205 patients with ICWR after mastectomy were retrospectively analyzed. Post-recurrence progression-free survival (PFS) and overall survival (OS) rates were calculated by Kaplan-Meier method and the differences were compared with Log-rank test. Competing risk model was used to estimate the subsequent regional recurrence (sRR) and locoregional recurrence (sLRR) rates, and the differences were compared with Gray test. Results: The 5-year sRR rate was 25.2% with median follow-up of 88.6 months. Of the 52 patients with sRR, 30 (57.7%) recurred in the axilla, 29 (55.8%) in supraclavicular fossa (SC), and five (9.6%) in internal mammary nodes. Surgery plus radiotherapy was independently associated with better sLRR and PFS rates (p<0.001). The ICWR interval of ≤ 4 years was associated with unfavorable sRR (p=0.062), sLRR (p=0.014), PFS (p=0.001), and OS (p=0.005). Among the 157 patients who received radiotherapy after ICWR, chest wall plus RNI significantly improved PFS (p=0.004) and OS (p=0.021) compared with chest wall irradiation alone. In the 166 patients whose ICWR interval was ≤ 4 years, chest wall plus RNI provided the best PFS (p<0.001) and OS (p=0.022) compared with chest wall irradiation alone or no radiotherapy. Conclusion: Patients with ICWR have a high-risk of sRR in SC and axilla. Chest wall plus RNI is recommended.